KONTRIBUSI PAJAK KENDARAAN BERMOTOR, BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH UPT MEDAN UTARA - , Fitri Yani Panggabean (Jurnal Akuntansi Bisnis dan Publik, 2020)
The purpose of this research is to test whether motor vehicle tax and motor vehicle tittle transfer fees have a significant effect local own-source revenue at the North Medan UPT Regional Tax and Retribution Management Agency and at the same time to find out how much motor vehicle tax contribution and the cost transferring the name of a motor vehicle for the local own-source revenue. The research method used is an associative research method by selecting samples using purposive sampling with a total sample of 24 samples from 2017-2018. The type of data used is quantitative data from the realization report of motor vehicle tax revenue, cost of motorized vehicle names and local own-source revenue. The data collected was analysed using the classical assumption testing method and hypothesis testing using the t test, f tes, and the coefficient of determination test. The results of the analysis show that a portion of motor vehicle tax and motor vehicle transfer costs have a significant influence on local own-source revenues. Simultaneously motor vehicle tax and motor vehicle transfer costs have a significant influence on local own-source revenue from the North Medan UPT Regional Tax and Retribution Management Agency .And the average contribution made by the motor vehicle tax to regional original income is 44.64%, while the contribution given by motor vehicle transfer fees to the regional original income is 53.93%.